Proceedings of the SIGCHI Conference on Human Factors in Computing Systems 2013
DOI: 10.1145/2470654.2481292
|View full text |Cite
|
Sign up to set email alerts
|

Accessible photo album

Abstract: While a photograph is a visual artifact, studies reveal that a number of people with visual impairments are also interested in being able to share their memories and experiences with their sighted counterparts in the form of a photograph. We conducted an online survey to better understand the challenges faced by people with visual impairments in sharing and organizing photos, and reviewed existing tools and their limitations. Based on our analysis, we developed an accessible mobile application that enables a v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…People with visual impairments take and share photographs for the same reasons that sighted people do [30,32], however, they encounter more challenges than sighted people both in taking photos and browsing their albums to select good photos [46,50]. Researchers have developed several methods to assist blind photography, including audio feedback that facilitates aiming the camera [32,45], and recorded memos and ambient sounds that augment photos [2,30]. Unlike this prior work on enhancing the photo-taking process, we focus on generating descriptions to help visually impaired people better browse and select photos for sharing.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…People with visual impairments take and share photographs for the same reasons that sighted people do [30,32], however, they encounter more challenges than sighted people both in taking photos and browsing their albums to select good photos [46,50]. Researchers have developed several methods to assist blind photography, including audio feedback that facilitates aiming the camera [32,45], and recorded memos and ambient sounds that augment photos [2,30]. Unlike this prior work on enhancing the photo-taking process, we focus on generating descriptions to help visually impaired people better browse and select photos for sharing.…”
Section: Related Workmentioning
confidence: 99%
“…Visually impaired people (both blind and low vision) have a strong presence on SNS and are interested in sharing photos [50]. They take photos for the same reasons that sighted people do: sharing daily moments with their sighted friends and family [30,32]. A prior study showed that visually impaired people shared a relatively large number of photos on Facebook-only slightly less than their sighted counterparts [50].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations